Yeast Lacking the PP2A Phosphatase Regulatory Subunit Rts1 Sensitizes rad51 Mutants to Specific DNA Damaging Agents - Aouida, Mustapha; Eshrif, Abdelmoez; Ramotar, Dindial (Frontiers in Genetics, 2019)
Rts1 is a regulatory subunit of the trimeric PP2A phosphatase and it participates in many biological processes by modulating the phosphorylation status of proteins. Consistent with its role, mutants lacking Rts1 display multiple phenotypes. We have previously performed a high throughput screen to search for yeast haploid mutants with altered sensitivity to the anticancer drug bleomycin, which acts by damaging the DNA to produce single and double strand breaks. RTS1 was amongst the genes that when singly deleted cause sensitivity to bleomycin. We investigate whether Rts1 plays a role in the repair of bleomycin-induced DNA lesions. We show that deletion of the RTS1 gene in the rad51 null background, lacking Rad51 known to be involved in the repair of bleomycin-induced DNA lesions, resulted in double mutants that were sensitized to bleomycin and not to other DNA damaging agents that creates DNA adducts. We further show that Rts1 has the ability to bind to DNA and in its absence cells displayed an increase in the frequency of both spontaneous and bleomycin-induced mutations compared to the parent. This is the first report implicating Rts1 with a role in DNA damage and repair, perhaps regulating the phosphorylation status of one or more proteins involved in the repair of DNA strand breaks.